Tunable Charge Transport in Hybrid Superlattices of Indium Tin Oxide Nanocrystals and Metal Phthalocyanines—Toward Sensing Applications. Issue 9 (26th February 2018) - Samadi Khoshkhoo, Mahdi; Joseph, Yvonne; Maiti, Santanu; Schreiber, Frank; Chassé, Thomas; Scheele, Marcus
Abstract: Macroscopic superlattices of tin‐doped indium oxide (ITO) nanocrystals (NCs) are prepared by self‐assembly at the air/liquid interface followed by simultaneous ligand exchange with the organic semiconductors M‐4, 4′, 4″, 4″′‐tetraaminophthalocyanine (M4APc, M = Cu, Co, Fe, Ni, Zn). Transport measurements, focusing on the effect of the metal center of the ligand, reveal a ligand‐dependent increase in electrical conductance by six to nine orders of magnitude, suggesting that M4APc provides efficient electronic coupling for neighboring ITO NCs. The resulting I–V characteristics as well as the temperature dependence (7–300 K) of the zero‐voltage conductance indicates that at low temperatures, transport across the arrays occurs via a sequence of inelastic cotunneling events, each involving ≈3 ITO NCs. At higher temperatures, a crossover to 3D Mott‐variable range hopping mechanism is observed. Finally, the vapor sensitivity of chemiresistors is investigated made from ITO NCs coupled via Cu‐ and Zn4APc by dosing the sensors with 4‐methyl‐2‐pentanone (4M2P), toluene, 1‐propanol, and water in the concentration range of 100–5000 ppm at 0% relative humidity. The nanocrystal superlattices respond with an increase in resistance to these analytes with the highest sensitivity to 4M2P. Abstract : Novel sensing materials, characterized by fast response, room‐temperature operability, and optical transparency, are developed based on the incorporation of phthalocyanine derivatives into indium tin oxide nanocrystal superlattices by self‐assembly at the liquid/air interface. Transport in the presented materials is described with multiple inelastic cotunneling, a mechanism in which local charging energies are mitigated by a series of simultaneous tunneling events.